Biliary ileus - Fillizzola, Roberto; Samaniego, Castor; Flores, Jorge; Román, Carlos; López, Roberto; Wattiez, Carlos Raúl; Bordón, Ana (Cirugía del Uruguay, 1998)
The authors present three cases of biliar i/eus diagnosed and treated.at the Servicio de Cirugía at the Primera Cátedra de Clínica Quirúrgica between December 1976 and August 1997, over a total of 3695 patients with biliar lithiasis. Enterolitotomy was performed in two patients; one of them is alive and we/1; the other, who underwent biliodigestive derivation six months later, died 14 years later due to septic complications of an hepatic abscess, and the third underwent enterolitotomy with fistula correction, dying eight days later due to pulmonary tromboembolism. Emphasis is made on diagnosis and time/y treatment. Final/y applicability of different therapeutical options is discussed.